Peak to average power reduction in OFDM - Sheheen Muhamed. (2008)
In this thesis, an overview of OFDM is discussed. It is followed by a brief survey of the most common techniques on PAPR reduction. A novel way of quantifying the distortion power when clipping is used for PAPR reduction is discussed through simulations. The major problems with the existing methods are bandwidth expansion and decreased data rate. Therefore the focus here is on a new technique called Carrier Interferometry OFDM (CI/OFDM) to enhance performance of OFDM systems without sacrificing bandwidth or data rate. Histogram of PAPR is used as a comparison tool to discuss the benefits of CI/OFDM against ordinary OFDM.